Ответы и объяснения

2012-11-25T13:12:00+00:00

x-y=2

xy=2

из первого выразим x=2+y и подставим во-второе

(2+y)y=2

2y+y2=2

y2+2y-2=0

D=4+4*2=12

y1=(-2-sqrt(12)/2=-2,7

y2=(-2+sqrt(12)/2=0,7

x-(-2,7)=2                                         x-0,7=2

x1=-0,7                                           x2=2,7

Ответ. x1=-0,7 , y1=-2,7, x2=2,7, y2=0,7

2012-11-25T14:50:57+00:00

{х-y=2 {x=2+y {x=2+y
{xy=2 {(2+y)*y=2 {2y+y^2=2

 

y2+2y-2=0

d=b^-4ac=4-4*(-2)=12

y1=-1+12/2

y2=-1-(12)/2

 

x-(-1+√12/2)=2    x=1-√12/2

x-(-1-√12/2)=2    x=1+√12/2

Ответ: (1-√12/2 ; -1+√12/2) и (1+√12/2 ; -1-√12/2)